1988
DOI: 10.1103/physrevc.37.1311
|View full text |Cite
|
Sign up to set email alerts
|

Unusual backward emission of multifragmentation products in ultrarelativistic nucleus-nucleus collisions

Abstract: Light fragments such as Na resulting from the multifragmentation of Au by 232-GeV ' 0 are emitted preferentially backwards in the laboratory system (F/B =0.81+0.05). This effect is not seen for similar products from V, Cu, or Ag targets, or for fission products from Au.Recent developments in particle accelerator technology have opened a new area of research involving ultrarelativistic nucleus-nucleus collisions at energies above 10AGeV. Of special interest to us was the opportunity to study target fragmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Using a thick-target thickcatcher technique, target-like fragments around A = 60, produced in the bombardment of gold by 12 C at 25 GeV [9], were found to be produced with mean velocity close to zero in the laboratory frame. An experiment of Loveland et al [10], based on the same technique, revealed a backward emission of 24 Na, produced by multi-fragmentation of gold by 16 O at 232 GeV. Results from a time-of-flight measurement [11] in a comprehensive projectilefragmentation experiment with a 197 Au beam of 600 A MeV and targets from carbon to lead showed a levelling off of the velocities of the fragments with increasing mass loss.…”
mentioning
confidence: 99%
“…Using a thick-target thickcatcher technique, target-like fragments around A = 60, produced in the bombardment of gold by 12 C at 25 GeV [9], were found to be produced with mean velocity close to zero in the laboratory frame. An experiment of Loveland et al [10], based on the same technique, revealed a backward emission of 24 Na, produced by multi-fragmentation of gold by 16 O at 232 GeV. Results from a time-of-flight measurement [11] in a comprehensive projectilefragmentation experiment with a 197 Au beam of 600 A MeV and targets from carbon to lead showed a levelling off of the velocities of the fragments with increasing mass loss.…”
mentioning
confidence: 99%